Escrever Leonilson: expansão do corpo, do desejo, da poesia - Marina Baltazar Mattos (2021)
This research seeks to discuss the deep connection that José Leonilson’s artistic work maintains with literature and poetic forms. The nonspecific and experimental practice in his works builds upon a contemporary trend of overflowing gender limits and discursive boundaries. The written word incorporation in his work is a constant in the midst of his drawings, paintings and embroidery, which points, more than to his constitutive restlessness – translated into the diversity of his artistic operations, developed in various supports, materials and procedures –, for a fundamental gesture: the inscription of the self, of the body, writing of life. The expansion movement, therefore, brings together and confuses not only the arts and materials, but the barriers that previously tried to contain the relationship between form and life, reality and fiction. This investigation was developed from theoretical movements of gesture, body, writing, diaries, illness, and readings that illuminate the affinities between work and life, reality and its fictionalization. Finally, the route’s guide reflects not only over some of Leonilson’s pieces, but through them, in a game between visible and sensitive, reaching parts of visibility, because its existence is in constant construction.